2003
DOI: 10.1126/science.301.5634.733
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Authors, Multiple Problems

Abstract: T he average number of authors on scientific papers is skyrocketing. That's partly because labs are bigger, problems are more complicated, and more different subspecialties are needed. But it's also because U.S. government agencies like the National Institutes of Health (NIH) have started to promote "team science." As physics developed in the post-World War II era, federal funds built expensive national facilities, and these served as surfaces on which collaborations could crystallize naturally. That has produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 0 publications
2
54
0
2
Order By: Relevance
“…This is of particular importance for junior researchers seeking promotion and tenure in fiercely competitive domains. Indeed, recent efforts by the National Institutes of Health to promote collaborative approaches to science sparked editorials in the high profile journals Science and Nature that listed numerous institutional disincentives for team science and questioned why any researcher would want to engage in collaborative work (Kennedy, 2003;"Who'd want to work in a team?," 2003).…”
Section: But…it Is Also Difficultmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of particular importance for junior researchers seeking promotion and tenure in fiercely competitive domains. Indeed, recent efforts by the National Institutes of Health to promote collaborative approaches to science sparked editorials in the high profile journals Science and Nature that listed numerous institutional disincentives for team science and questioned why any researcher would want to engage in collaborative work (Kennedy, 2003;"Who'd want to work in a team?," 2003).…”
Section: But…it Is Also Difficultmentioning
confidence: 99%
“…From work by Hagstrom (1965) and Beaver (2001) we know that one important dimension of collaboration propensity is whether or not researchers believe collaboration will provide them with access to expertise, experimental apparatus, data sets and other scarce resources that are useful or necessary in answering research questions of interest. At the same time, it has been suggested that collaboration in some fields can mask individual achievement and make it difficult to receive recognition for one's efforts via employment offers, promotion and tenure, and important prizes (Kennedy, 2003;Knorr Cetina, 1999;"Who'd want to work in a team?," 2003). Thus, the second aspect of collaboration propensity is the extent to which researchers perceive collaboration as a component of a viable career path, which they think will lead them to success.…”
Section: Collaboration Propensitymentioning
confidence: 99%
“…[1][2][3][4][5] Indeed, data suggest that coauthorship has increased during the past 20 years, yet the reasons behind this increase remain controversial. [3][4][5][6][7] Since 1978, the group currently known as the International Committee of Medical Journal Editors (ICMJE) has met to enact uniform requirements for manuscripts submitted to biomedical journals. Although the initial intent of the ICMJE was to consolidate publication format, its scope has broadened throughout the years to include ethical issues surrounding authorship standards.…”
mentioning
confidence: 99%
“…Next, we identified the orders of authors, and set placement=1 if there was only one author in the article. Since several works believed that the first author is usually the person who has taken the most responsibility and work (Reisenberg & Lundberg, 1990;Kennedy, 2003;Rennie et al, 1997;Mattsson et al, 2011), we placed more weight to the first author when there were more than one authors contained in an article. The placement is thus calculated as below:…”
Section: Contribution Scorementioning
confidence: 99%